2019
DOI: 10.1007/s42452-019-1750-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cesium and cationic mineral elements in napiergrass

Abstract: Napiergrass is fast-growing perennial known for its high potential for accumulation of cesium (Cs). Cs is highly mobile within a plant and can be distributed to various plant organs. Here, we investigated the distribution of cesium-133 (133 Cs) and competitively translocated cationic minerals, such as potassium (K), calcium (Ca), and magnesium (Mg), in different organs of napiergrass. Treatments comprised four concentrations of 133 Cs applied to soil: 0 (as control); 300; 500; and 1000 μM. Leaf blades containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The same dependence was also reported to be attributed to other metals, e.g., Co [43]. However, the non-even distribution of Cs-133 in plant organs with greater amounts of Cs in younger parts of stems and leaf blades indicated the selective sorption of Cs by plants [4]. Vacula et al [15] recently reported on Cs accumulation by C. demersum L. under laboratory and field conditions with a Cs concentration range comparable with that in our study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The same dependence was also reported to be attributed to other metals, e.g., Co [43]. However, the non-even distribution of Cs-133 in plant organs with greater amounts of Cs in younger parts of stems and leaf blades indicated the selective sorption of Cs by plants [4]. Vacula et al [15] recently reported on Cs accumulation by C. demersum L. under laboratory and field conditions with a Cs concentration range comparable with that in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, a large amount of data on this topic was reported by Japanese researchers due to their experience with nuclear incidents affecting the release of Cs radionuclides into the environment. The Fukushima Daiichi Nuclear Power Plant disaster in 2011 resulted in radioactive caesium adsorption by soil and plants as a result of the transfer of radionuclides to livestock [1][2][3][4][5]. Other sites of nuclear mishaps, e.g., Ignalina [6] and Chernobyl, have been reported [7,8].…”
Section: Introductionmentioning
confidence: 99%